The Index Seminum: Seeds of change for seed exchange. Issue 2 (3rd April 2016) - Havinga, Reinout; Kool, Anneleen; Achille, Frédéric; Bavcon, Jože; Berg, Christian; Bonomi, Costantino; Burkart, Michael; De Meyere, Dirk; Hart, Joke 't; Havström, Mats; Keßler, Paul; Knickmann, Barbara; et al.
Abstract: Botanic gardens have been exchanging seeds through seed catalogues for centuries. In many gardens, these catalogues remain an important source of plant material. Living collections have become more relevant for genetic analysis and derived research, since genomics of non‐model organisms heavily rely on living material. The range of species that is made available annually on all seed lists combined, provides an unsurpassed source of instantly accessible plant material for research collections. Still, the Index Seminum has received criticism in the past few decades. The current exchange model dictates that associated data is manually entered into each database. The amount of time involved and the human errors occurring in this process are difficult to justify when the data was initially produced as a report from another database. The authors propose that an online marketplace for seed exchange should be established, with enhanced search possibilities and downloadable accession data in a standardised format. Such online service should preferably be supervised and coordinated by Botanic Gardens Conservation International (BGCI). This manuscript is the outcome of a workshop on July 9th, 2015, at the European botanic gardens congress "Eurogard VII" in Paris, where the first two authors invited members of the botanic garden community to discuss how the anachronistic Index Seminum can be transformed into an improved and modern tool for seed exchange.